Dynamic changes in immune cell populations by AXL kinase targeting diminish liver inflammation and fibrosis in experimental MASH - Grøndal, Sturla Magnus; Tutusaus, Anna; Boix, Loreto; Reig, Maria; Blø, Magnus; Hodneland, Linn; Gausdal, Gro; Jackson, Akil; Garcia de Frutos, Pablo; Lorens, James Bradley; Morales, Albert; Marí, Montserrat (Frontiers in Immunology, 2024)
Background & Aims: Metabolic dysfunction-associated steatohepatitis (MASH) is a significant health concern with limited treatment options. AXL, a receptor tyrosine kinase activated by GAS6 ligand, promotes MASH through the activation of hepatic stellate cells and inflammatory macrophages. This study identified cell subsets affected by MASH progression and the effect of AXL inhibition. Methods: Mice were fed chow, or different fat-enriched diets to induce MASH and small molecule AXL kinase inhibition with bemcentinib was evaluated. Gene expression was measured by qPCR. Time-of-flight mass cytometry (CyTOF) used single cells from dissociated livers, acquired on the Fluidigm Helios and cell populations studied using machine learning.Results: In mice fed different fat-enriched diets, liver steatosis alone was insufficient to elevate plasma soluble AXL (sAXL) levels. However, in conjunction with inflammation, sAXL increases, serving as an early indicator of steatohepatitis progression. Bemcentinib, an AXL inhibitor, effectively reduced pro-inflammatory responses in MASH models, even before fibrosis appearance. Utilizing CyTOF analysis, we detected a decreased population of Kupffer cells during MASH while promoting infiltration of monocytes/macrophages and CD8+ T-cells. Bemcentinib partially restored Kupffer cells, reduced pDCs and GzmB-NK cells, and increased GzmB+CD8+T-cells and LSECs. Additionally, AXL inhibition enhanced a subtype of GzmB+CD8+ tissue resident memory T-cells characterized by CX3CR1 expression. Furthermore, bemcentinib altered the transcriptomic landscape associated with MASH progression, particularly in TLR signalling and inflammatory response, exhibiting differential cytokine expression in plasma, consistent with liver repair and decreased inflammation. Conclusions: Our findings highlight sAXL as a biomarker for monitoring MASH progression and demonstrate that AXL targeting shifted liver macrophages and CD8+T-cell subsets away from an inflammatory phenotype towards fibrotic resolution and organ healing, presenting a promising strategy for MASH treatment.